Role of sphingosine 1-phosphate receptors, sphingosine kinases and sphingosine in cancer and inflammation. (January 2016) - Pyne, Nigel J.; McNaughton, Melissa; Boomkamp, Stephanie; MacRitchie, Neil; Evangelisti, Cecilia; Martelli, Alberto M.; Jiang, Hui-Rong; Ubhi, Satvir; Pyne, Susan
Abstract: Sphingosine kinase (there are two isoforms, SK1 and SK2) catalyses the formation of sphingosine 1-phosphate (S1P), a bioactive lipid that can be released from cells to activate a family of G protein-coupled receptors, termed S1P1-5 . In addition, S1P can bind to intracellular target proteins, such as HDAC1/2, to induce cell responses. There is increasing evidence of a role for S1P receptors (e.g. S1P4 ) and SK1 in cancer, where high expression of these proteins in ER negative breast cancer patient tumours is linked with poor prognosis. Indeed, evidence will be presented here to demonstrate that S1P4 is functionally linked with SK1 and the oncogene HER2 (ErbB2) to regulate mitogen-activated protein kinase pathways and growth of breast cancer cells. Although much emphasis is placed on SK1 in terms of involvement in oncogenesis, evidence will also be presented for a role of SK2 in both T-cell and B-cell acute lymphoblastic leukemia. In patient T-ALL lymphoblasts and T-ALL cell lines, we have demonstrated that SK2 inhibitors promote T-ALL cell death via autophagy and induce suppression of c-myc and PI3K/AKT pathways. We will also present evidence demonstrating that certain SK inhibitors promote oxidative stress and protein turnover via proteasomal degradative pathways linked with induction of p53-and p21-induced growth arrest. In addition, the SK1 inhibitor, PF-543 exacerbates disease progression in an experimental autoimmune encephalomyelitis mouse model indicating that SK1 functions in an anti-inflammatory manner. Indeed, sphingosine, which accumulates upon inhibition of SK1 activity, and sphingosine-like compounds promote activation of the inflammasome, which is linked with multiple sclerosis, to stimulate formation of the pro-inflammatory mediator, IL-1β. Such compounds could be exploited to produce antagonists that diminish exaggerated inflammation in disease. The therapeutic potential of modifying the SK-S1P receptor pathway in cancer and inflammation will therefore, be reviewed.